A new genus and species of winter stoneflies (Plecoptera: Capniidae) from Southwest China, with a commented checklist of the family in the Oriental Realm - Murányi, Dávid; Li, Weihai; Yang, Ding (Zootaxa, 2015)
A new genus and species of the family Capniidae (Plecoptera), Sinocapnia kuankuoshui gen. n., sp. n. is described from the adult male and a female collected in Guizhou Province of southwest China. The new taxon is distinguished from all extant Capniidae genera and the assemblage of species currently included in Capnia sensu lato by combination of unique genitalic, wing, and thoracic sclerites characters. No closely related taxon is indicated on the basis of morphological characters. An annotated checklist of the family Capniidae from the Oriental Realm is given.